PEMBELAJARAN BAHASA ARAB DI MADRASAH ALIYAH: ARABIC LEARNING IN MADRASAH ALIYAH - Andry Eka Setiyawan; Akla; Walfajri (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2021)
Abstract: This study aimed to determine how the Arabic learning process of students and how the Arabic learning outcomes level of students in Islamic Senior High School. This study used a combined research method. Quantitative method was used to collect data from the learning process, while quantitative method was used to determine learning outcomes. This research was conducted at Islamic Senior High School 1 Metro with 35 students sample of grade X. The method of data collection used observation, interviews and tests. Data analysis techniques in qualitative data used descriptive analysis. Quantitative data analysis used quantitative descriptive analysis. The results showed that the teachers’ learning process has involved students’ active learning. Teachers used teaching methods and strategies that were relevant to the material. The availability of learning media was adequate, but teachers had a limited ability to use media, especially in technology-based media. The results of the statistical analysis showed that the average Arabic learning outcomes of students 78.54 was in the enough range. Learning outcomes that had not reached the maximum range due to lack of synergy between learning components, especially the use of technology-based media.